Upgrading Biocrude of Grindelia Squarrosa to Jet Fuel Precursors by Aqueous Phase Hydrodeoxygenation. Issue 9 (8th August 2018) - Yang, Xiaokun; Pereira, Marcus V.; Neupane, Bishnu; Miller, Glenn C.; Poulson, Simon R.; Lin, Hongfei
Abstract: Bio‐jet fuel is increasingly attracting attention in attempts to reduce the environmental impacts of aviation fuels. Feedstocks like camelina, jatropha and algae have been extensively studied, and exhibit fair performance in producing low‐density hydrocarbon biofuels, mainly from triglyceride lipids. Grindelia squarrosa is a promising feedstock since the primary diterpenoid, grindelic acid with the branched tricyclic structure, is the major component in its biocrude. Herein, a heterogeneous bi‐functional catalyst, palladium with the reductive properties supported on tungstate zirconia with acidic properties and good stability in hydrothermal media, was used for the conversion of Grindelia squarrosa biocrude to potential bio‐jet fuels. Different solid acid catalyst supports and a variety of reaction conditions, such as temperature, catalyst loading, hydrogen pressure, and reaction time, were systematically investigated. At the optimum conditions, the oxygen content deceased from 18.1 % in the Grindelia squarrosa biocrude feedstock to 5.6 % in the final product, and is ready for further industrial treatment. The upgrading method utilized in this work can produce jet fuel precursors for synthesizing high‐density cyclic hydrocarbons. Abstract : Grindelia squarrosa is a potential feedstock for producing high heating value biofuels. Herein, by using a 1 % Pd/W‐ZrO2 bi‐functional heterogeneous catalyst, Grindelia biocrude was successfully converted to partially saturated cyclic hydrocarbon products containing 14∼16 carbons that had a low oxygen content (5.6 %) under the optimum reaction conditions.